Effect of Some Antioxidants on the Hematological and Biochemical Blood Parameters of Awassi Rams (NTU Journal of Agriculture and Veterinary Science, 2022)
In this study, (24) Awassi rams were used at the age of (1.5-2 years), with an average weight of (46.4 kg) to study the effect of giving some antioxidants on hematological and blood biochemical on Awassi rams , The rams were randomly allotted into four groups of equal number (6) rams each group , the first group (control) , the second group was given turmeric at the rate of 3 g / kg feed / head daily, the third group was supplemented orally with 400 IU vitamin E / head three times a week , the fourth group was supplemented orally with 400 mg CoQ10 coenzyme / head three times a week , and these materials were given to the rams of each treatment before providing the daily feed to the animals , The experimental animals were given a standardized diet consisting of ( concentrated feed + Wheat Straw ) on the basis of 2.5 % of live body weight . The percentage of protein in the diet was 15.22% and the metabolic energy was (2721.5) kcal / kg of feed. The weights of the animals were measured and blood samples were drawn from the jugular vein every month to measure the characteristics of the physical and biochemical parameters of the blood in the blood serum. The results of the study showed a significant (p?0.01) effect of the treatments on the characteristics of the animal’s weight, number of WBC, the percentage of eosinophil's and basophils than control group , while the treatments did not show a significant effect on the other blood values. The results also showed a significant effect of the treatments on the level of concentration of total protein, cholesterol, triglycerides, globulin and urea, in addition to the levels of HDL, LDL , While there was no significant effect of the treatments on the concentration of glucose, albumin, VLDL in the blood plasma. Through the results of this study, we conclude that giving antioxidants to rams had a positive effect on some physical, biochemical and enzymatic parameters of blood in the treated groups compared to the control.